2015
DOI: 10.12998/wjcc.v3.i6.484
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell arteritis: Current treatment and management

Abstract: Glucocorticoids remain the cornerstone of medical therapy in giant cell arteritis (GCA) and should be started immediately to prevent severe consequences of the disease, such as blindness. However, glucocorticoid therapy leads to significant toxicity in over 80% of the patients. Various steroid-sparing agents have been tried, but robust scientific evidence of their efficacy and safety is still lacking. Tocilizumab, a monoclonal IL-6 receptor blocker, has shown promising results in a number of case series and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 90 publications
1
37
0
12
Order By: Relevance
“…On the other hand, indicators of an enhanced systemic inflammatory response may lead to an earlier diagnosis and timely treatment, thus preventing ischemic complications [23]. There have been reports indicating the usefulness of serological acute phase (ESR and CRP) and inflammatory markers (IL-6) for the course during therapy of GCA [17,19,24]. However, there is still a paucity of valid serological markers strongly needed for monitoring GCA relapse and complications [21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, indicators of an enhanced systemic inflammatory response may lead to an earlier diagnosis and timely treatment, thus preventing ischemic complications [23]. There have been reports indicating the usefulness of serological acute phase (ESR and CRP) and inflammatory markers (IL-6) for the course during therapy of GCA [17,19,24]. However, there is still a paucity of valid serological markers strongly needed for monitoring GCA relapse and complications [21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports indicating the usefulness of serological acute phase (ESR and CRP) and inflammatory markers (IL-6) for the course during therapy of GCA [17,19,24]. However, there is still a paucity of valid serological markers strongly needed for monitoring GCA relapse and complications [21,[24][25][26]. Therefore, we set out to measure and analyze serological analytes in a large cohort of clinically wellcharacterized untreated GCA patients that could help clinicians evaluate the course of the disease, including relapse/ complications.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is implemented especially in developing symptomatic aneurysms in large vessel involvements. In the case of the development of artery stenosis other than this, interventions such as "stent," "bypass," or "angioplasty" can be applied (10). Most interestingly, even if no treatment applied, spontaneous remission can be seen in some patients (2).…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin use is controversial; however, it remains in the recommendations where there is no contraindication. Some retrospective analyses have found that aspirin is protective against cerebrovascular and cardiovascular events .…”
Section: Ongoing Managementmentioning
confidence: 99%